Molecular docking of two cytotoxic compounds from Calotropis gigantea leaves against therapeutic molecular target of pancreatic cancer - Purnama, Agnia; Mardina, Vivi; Puspita, Kana; Qanita, Intan; Rizki, Diva R.; Hasballah, Kartini; Iqbal, Mudassar; Sarong, Murniana (Narra Sains Indonesia, 2021)
The utilization of natural compounds as therapeutic agents to treat pancreatic cancer has recently focused on natural drug research. Calotropis gigantea has long been believed to be a medicinal plant that helps in treating various diseases. The bioactive compounds 9-metoxipinoresinol and isoliquiritigenin isolated from C. gigantea leaves are proven to act as therapeutic agents by inhibiting the cancer cell growth of Panc-1 cells. This study aimed to screen the potential molecular inhibition mechanisms of 9-metoxipinoresinol and isoliquiritigenin against pancreatic cancer development in-silico. We analyzed the activity of the aforementioned two compounds as inhibitors of several proteins that play a role in the growth of pancreatic cancer cells, such as GCNT3, GOT1, c-Met, PPARγ, BUB1, and NF-κβ, through molecular docking investigation. Our data suggested that 9-metoxipinoresinol and isoliquiritigenin were able to have well interaction with the target proteins, in which the predicted affinity energy ranged between -6.8 and 8.7 kcal/mol. The docking scores of 9-metoxipinoresinol and isoliquiritigenin were higher than the standard drug used (gemcitabine). Based on the binding affinity energy, GCNT3 and BUB1 are potentially to be used as target molecules for cancer therapy using 9-metoxipinoresinol and isoliquiritigenin, respectively.